Hello App Inventor! Android programming for kids and the rest of us - Beer, Paula 1995-; Simmons, Carl (Manning, 2015)
Hello App Inventor! introduces creative young readers to the world of mobile programming -- no experience required! Featuring more than 30 fun invent-it-yourself projects, this full-color, fun-to-read book starts with the building blocks you need to create a few practice apps. Then you'll learn the skills you need to bring your own app ideas to life.
Includes index. - Print version record
Keywords: Android (Electronic resource); Application software -- Development; Mobile computing; Logiciels d'application; Développement; Informatique mobile; Application software; Development; Engineering & Applied Sciences; Computer Science